The interface between matrix pockets and fibre bundles under impact loading - Gerlach, R; Pabst, A; Petrinic, N; Hornig, A; Wiegand, J; Siviour, C; Hufenbach, W (2009)
The response of the interface between matrix pockets and infiltrated fibre bundles, often encountered in 3D woven composites, has been investigated experimentally. Fibre bundle pull out tests have been performed along with tensile experiments measuring the normal strength of the interface at quasi-static and high loading rates. The purpose of this study was to generate information that is necessary to numerically model 3D woven composite materials on the meso scale (yarns, matrix pockets and yarn-matrix interface). The experiments show an increase of the interface strength for both the pull out tests and the tensile tests with loading rate. Failure for the pull out experiments always propagated along the interface between fibre bundle and matrix. However, failure for the tensile tests occurred both at the interface and within the yarn, at approximately the same level of stress. It is therefore concluded that the interface between matrix pocket and yarn can be assumed to have the properties of the bulk yarn material, and does not need to be modelled explicitly. © 2009 Elsevier Ltd. All rights reserved.